Inheritance Study for Fusarium Wilt Resistance in Pigeonpea (Cajanus cajan L. Millspaugh) - Latha, V. Swarna; Kumar, M. V. Nagesh; Reddy, K. Dharma (International Journal of Bio-resource and Stress Management, 2023)
Wilt caused by Fusarium udum Butler, is one of the most important limiting factors for pigeonpea production. In order to incorporate Fusarium wilt resistance into adapted, popular, high yielding but susceptible variety PRG-100, the inheritance of resistance to Fusarium wilt in pigeonpea was studied using ICP-8863 and ICPL-87119 as resistant parents and PRG-100 as susceptible parent. Analysis of F2 progenies of the cross PRG-100 x ICP-8863 showed a digenic epistatic interaction mechanism of resistance with a 13 (resistant): 3 (susceptible) segregation ratio. Similarly, evaluation of F2’s of the cross PRG-100 x ICPL-87119 also showed digenic epistatic interaction which segregated in 9 (resistant): 7 (susceptible) ratio, indicating a complementary gene action. Study of progenies back crossed to resistant parents indicated the segregation of resistant and susceptible progeny in the ratio of 3R:1S in both the crosses. The allelic test between ICP-8863 and ICPL-87119 confirmed the independence of genes governing resistance.